School Digital Transformation and Principal Leadership in Improving Teacher Professionalism - Wahyuning Widyawati; Saryanto Saryanto; Rahmat Mulyono (CV Edujavare Publishing, 2026)
In this context, principals play a strategic role as key decision-makers who guide the direction of school innovation and ensure that digital initiatives are effectively implemented to improve educational quality. This study aims to analyze school digital transformation and principal leadership in improving teacher professionalism at SD Negeri 1 Rimpak in the 2025/2026 academic year. This study uses a qualitative case study approach involving the principal, teachers, and relevant stakeholders as research participants. Data were collected through interviews, classroom observations, and document analysis, then analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings show that school digital transformation significantly contributes to improving teacher professionalism by enhancing digital literacy, pedagogical innovation, and instructional effectiveness. Furthermore, principal leadership plays a crucial role in driving this transformation through vision building, professional development programs, collaborative culture development, instructional supervision, and resource management. Although several challenges such as differences in teacher digital competence and limited infrastructure were identified, effective and adaptive leadership was found to help overcome these barriers. The study concludes that digital transformation and principal leadership are interrelated factors that jointly strengthen teacher professionalism and improve the overall quality of education in primary schools.